Voluntary wheel running ameliorated the deleterious effects of high-fat diet on glucose metabolism, gut microbiota and microbial-associated metabolites - Ling Zhang; Wenyu Zou; Yongyan Hu; Honghua Wu; Ying Gao; Junqing Zhang; Jia Zheng (Food Science and Human Wellness)
Exercise training is critical for the early prevention and treatment of obesity and diabetes mellitus. However, the mechanism with gut microbiota and fecal metabolites underlying the effects of voluntary wheel running on high-fat diet induced abnormal glucose metabolism has not been fully elaborated. C57BL/6 male mice were randomly assigned to 4 groups according to diets (fed with normal chow diet or high-fat diet) and running paradigm (housed in static cage or with voluntary running wheel). An integrative 16S rDNA sequencing and metabolites profiling was synchronously performed to characterize the effects of voluntary wheel running on gut microbiota and metabolites. It showed that voluntary wheel running prevented the detrimental effects of high-fat feeding on glucose metabolism. 16S rDNA sequencing showed remarkable changes in Rikenella and Marvinbryantia genera. Metabolic profiling indicated multiple altered metabolites, which were enriched in secondary bile acid biosynthesis signaling. In conclusion, our study indicated that voluntary wheel running significantly improved glucose metabolism and counteracted the deleterious effects of high-fat feeding on body weight and glucose intolerance. We further found that voluntary wheel running could integratively program gut microbiota composition and fecal metabolites changes, and may regulate muricholic acid metabolism and secondary bile acid biosynthesis in high-fat fed mice.